PENGARUH PEMAHAMAN SISWA AKIBAT MISKONSEPSI MATERI HIMPUNAN PADA BUKU MATEMATIKA KELAS 7 - Fanden Batara Damanik; Yogi Okta Fernandes Sembiring; Desti Cantik Novita Sari; Fasya Nabilah Putri; Noviantri Lumban Raja; Wingston Leonard Sihombing (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Misconception is one of the serious obstacles in mathematics learning. Sets material, especially the concepts of the empty set and the universal set, often become sources of misconception for students. Main learning sources such as textbooks play a large role in shaping this conceptual understanding. This study aims to analyze and identify potential misconceptions in the material on the empty set and the universal set in 7th grade mathematics textbooks, as well as the possible impacts on students. The method used is descriptive qualitative through literature study and content analysis. The material analyzed in this study is the “Set Theory” chapter in the “Mathematics Grade VII Semester 1” textbook published by the Ministry of Education and Culture. The results show that although the book has defined the empty set, the explanation is not sufficiently complete and in depth. The absence of an explicit explanation that the empty set is a subset of every set, including the universal set, potentially causes misconception. As a result, students may experience misunderstanding of basic concepts, difficulties in set operations, and confusion in interpreting the universal set. It is concluded that the presentation of empty set material in the textbook needs improvement by giving more comprehensive explanations and contextual examples to prevent misconceptions. The implication of this study is the importance of a strict review of textbook material to ensure the accuracy of the concepts conveyed.